2020
DOI: 10.1007/s12105-019-01125-y
|View full text |Cite|
|
Sign up to set email alerts
|

Human Papillomavirus and Factors Associated with Recurrence in Sinonasal Inverted Papillomas from Poland and Spain

Abstract: Sinonasal inverted papilloma (SNIP) is a benign but locally aggressive tumor that has a tendency for recurrence and malignant transformation. The role of human papillomavirus (HPV) in SNIP is controversial. To determine the HPV-DNA prevalence and type distribution in SNIP in two different geographic areas and assess the association between SNIP recurrence and HPV infection, as well as additional potential etiologic factors. Two retrospective cohorts of SNIP patients from Poland and Spain were evaluated. Demogr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 27 publications
0
15
0
2
Order By: Relevance
“…58 In a study of 28 IPs, Lin et al made the same conclusion. 59 However, Fulla et al, 60 Roh et al 61 and Stoddard et al 48 all found no association between HPV infection and recurrence of IP disease. This demonstrates that overall evidence for this association is, again, conflicting.…”
Section: The Significance Of Hpv In Progression Of Ip Diseasementioning
confidence: 98%
“…58 In a study of 28 IPs, Lin et al made the same conclusion. 59 However, Fulla et al, 60 Roh et al 61 and Stoddard et al 48 all found no association between HPV infection and recurrence of IP disease. This demonstrates that overall evidence for this association is, again, conflicting.…”
Section: The Significance Of Hpv In Progression Of Ip Diseasementioning
confidence: 98%
“…Desde el punto de vista fisiopatológico algunos autores han propuesto que el VPH tendría un rol en la etiología del papiloma invertido y progresión a carcinoma escamoso, particularmente a través del aumento de expresión de EGFR [20][21][22] . Sin embargo, estudios retrospectivos con muestras tumorales describen una positividad del 5,1%-13% para la presencia de VPH en general, 5%-6% para VPH-AR; baja correlación entre la inmunohistoquímica para p16 y la presencia de VPH en estos tumores, además de no existir relación entre el virus y la recurrencia o desarrollo de carcinoma escamoso 19,23,24 . En conclusión, no es posible establecer al VPH como un factor etiológico ni de progresión en papiloma invertido.…”
Section: Papiloma Invertidounclassified
“…Regelmäßiger Alkoholkonsum hat keinen Einfluss auf die Rezidivrate [11,15] oder die maligne Entartung (▶ Tab. 2) sinunasaler Papillome.…”
Section: Extrinsische Risikofaktorenunclassified